2016
DOI: 10.1080/2162402x.2016.1149667
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by MYB is associated with tumor relapse in patients with early stage colorectal cancer

Abstract: The presence of tumor immune infiltrating cells (TILs), particularly CD8+ T-cells, is a robust predictor of outcome in patients with colorectal cancer (CRC). We revisited TIL abundance specifically in patients with microsatellite stable (MSS) CRC without evidence of lymph node or metastatic spread. Examination of the density of CD8+ T-cells in primary tumors in the context of other pro-oncogenic markers was performed to investigate potential regulators of TILs. Two independent cohorts of patients with MSS T2-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…As we and others previously reported that high c-Myb expression in CRC cell lines enhanced their chemorezistance 24-26, the „metastasis hypothesis“ seems to be more relevant. It should be noted, however, that high c-Myb protein level was associated with poor prognosis in gallbladder adenocarcinoma 27, 28 and esophageal squamous cell carcinoma 29 and two previous studies by Ramsay group reported that high c-Myb associates with poor prognosis in CRC patients 30, 31. While Millen et al found an association between c-Myb level and relapse-free survival in a small cohort of preselected CRC patients (only T2 patients, cases with deficient mismatch repair excluded) 30, Biroccio et al reported a relation between c-Myb, DFS and OS in a 91 CRC patients (70 colon, 21 rectum) without any preselection 31.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…As we and others previously reported that high c-Myb expression in CRC cell lines enhanced their chemorezistance 24-26, the „metastasis hypothesis“ seems to be more relevant. It should be noted, however, that high c-Myb protein level was associated with poor prognosis in gallbladder adenocarcinoma 27, 28 and esophageal squamous cell carcinoma 29 and two previous studies by Ramsay group reported that high c-Myb associates with poor prognosis in CRC patients 30, 31. While Millen et al found an association between c-Myb level and relapse-free survival in a small cohort of preselected CRC patients (only T2 patients, cases with deficient mismatch repair excluded) 30, Biroccio et al reported a relation between c-Myb, DFS and OS in a 91 CRC patients (70 colon, 21 rectum) without any preselection 31.…”
Section: Discussionmentioning
confidence: 88%
“…It should be noted, however, that high c-Myb protein level was associated with poor prognosis in gallbladder adenocarcinoma 27, 28 and esophageal squamous cell carcinoma 29 and two previous studies by Ramsay group reported that high c-Myb associates with poor prognosis in CRC patients 30, 31. While Millen et al found an association between c-Myb level and relapse-free survival in a small cohort of preselected CRC patients (only T2 patients, cases with deficient mismatch repair excluded) 30, Biroccio et al reported a relation between c-Myb, DFS and OS in a 91 CRC patients (70 colon, 21 rectum) without any preselection 31. Although there are some differences in design of our study and that of Biroccio group (inclusion of patients with tumor localized in rectum by Biroccio et al, different proportions of patients in group T1/T2 vs T3/T4, the length of follow-up, immunohistochemistry protocol etc.)…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Paradoxically, patients with CRC and high MYB expression exhibit low incidence of distant metastases [38] and favorable clinical prognosis tumor immune infiltrating cells and a clinical history of longer relapse-free survival were related to high expression of MYB. An immunomodulatory effect conferred by MYB was also observed in CD8 + TILs in the murine CRC model [40]. CDX-2 encodes a regulator of intestinespecific genes involved in cell growth and differentiation.…”
Section: Discussionmentioning
confidence: 88%
“…Overexpression of the MYB transcription factor (+ 28.8-fold expression in knockout cells) has been associated with poor prognosis and was frequently observed in colorectal cancer (CRC) (Cross et al 2015 ). Another study pointed out that MYB expression in tumor cells due to its tumorigenic role modulated the host immune response, which has the potential to influence the use of immunotherapy in CRC patients (Millen et al 2016 ). MYC (+ 5.1-fold) is another transcription factor with a critical role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%